Global buckling of a thin-walled T-frame with consideration of the shear effect - Magnucki, Krzysztof; Jasion, Paweł (Engineering Transactions, 2026)
The work concerns the global elastic buckling problem of a thin-walled T-frame with consideration of the shear effect. A novel approach was used to account for this effect namely the non-linear shear deformation theory which gives as a result the shear deformation function describing the behaviour of the beam cross-section. This thin-walled T-frame consists of horizontal beam and vertical column made of the same standard H-beams. The shape of this standard H-beam and the dimensionless deformation function of the plane cross-section, being the result of the shear effect, are analytical described. The buckling problem of the frame is analytically formulated and solved. The critical loads of exemplary beams are analytically determined. Moreover, a numerical FEM model of the frame is elaborated and the critical loads of exemplary frames are determined. Consequently, the research results obtained by both methods are compared and the advantages of the proposed approach is discussed.